OA52 "ethics from the bottom up": promoting networks and participation through shared stories of care. Issue Volume 5: Issue (2015)Supplement 1 (1st April 2015) - Schuchter, Patrick; Heller, Andreas
Abstract : Background: The "basic action" in creating compassionate communities is to create settings where people effectively have the opportunity to develop concerns and compassion for each other. The project "ethics from the bottom up" (in Bad Bentheim, Lower Saxony, Germany) brings together the relatives of old and dying people, professionals from healthcare organisations and people from other living and working contexts in order to share their sorrows and care experiences. Aim: Current methods and concepts of applied and organised ethical deliberation (or ethics "consultation") are not qualified and able to fulfil the requirements of ethical questions in the field of health promotion and health promoting palliative care. The predominant model of ethical deliberation in healthcare settings, the clinical ethics consultation, is designed for the specific orientation needs of curative medicine. The analogous step from medicine to health promotion, from professional palliative care to compassionate communities has not been carried out in ethics. By promoting a compassionate community through shared narratives of care and concern, a paradigmatic shift from clinical ethics to "communal" ethics is put into action. Method: Participatory action research design. Ethical approach based on narrative and care ethics. Results: We observe a new and simple way to bring relatives into communication with each other and with professional and (specialised) health services and to discuss the fundamental questions of human life. This is one way of initiating the democratisation of care, of finding support in the challenges of weakness and dying. Conclusion: In contrast to a narrowing tendency in modern ethics/ethics consultation (focus on moral dilemmas and treatment decisions) the objective of ethical deliberation is not just a singular decision but the sustainable cultivation of collective practical wisdom in a web of meaningful relationships.